Multi-Phenotypic Breast Cancer Post-Radiotherapy for Hodgkin Lymphoma: A Case of Secondary Malignancy - Donnell White PhD; Maryam Sadough Shahmirzadi MD; Brian Boulmay MD (SAGE Publishing, 2023)
Morbidity and mortality associated with radiation-induced secondary malignancies (RISMs) have shifted treatment paradigms to minimize or eliminate radiation from treatment regimens. In this case, a 48-year-old woman was diagnosed with Hodgkin lymphoma (HL) and treated with radiotherapy in 2000. In 2018, she was diagnosed with ductal carcinoma in situ (DCIS) of the right breast and treated with a mastectomy. Soon after, she developed triple-negative invasive ductal carcinoma (IDC) in her reconstructed breast. The patient underwent a left lumpectomy, and pathology showed ER-/PR-/HER2+ IDC. This patient's multi-phenotypic DCIS and IDC presentation are suspected to be RISM due to her previous HL treatment regimen.